A Prospective Study to Evaluate the Prevalence of Microsatellite Instability in Endometrial Carcinoma by using Immunohistochemistry for Mismatch Repair Proteins as a Surrogate Marker - Prithviraj K. Solanki; Mahesh Mandolkar; Padmaj Kulkarni (Indian Journal of Medical and Paediatric Oncology)
Aim Use of immunohistochemistry for mismatch repair (MMR) proteins to identify the prevalence of microsatellite instability (MSI) in cases of endometrial carcinoma and its subsequent correlation with various histopathological parameters.